KEBAKARAN LAHAN BASAH DAN FAKTOR MANUSIA SEBAGAI PENYEBABNYA - Ali Alamsyah Siregar; Mona Lestari; Novrikasari Novrikasari; Dini Arista Putri; Desheila Andarini; Rizka Faliria Nandini (Universitas Lambung Mangkurat, 2021)
Currently, forest and land fires have become a regular disaster in Indonesia. The cause of the fires was mostly due to human factors. Ogan Ilir is an area with forest and land fires every year because its dominated by wetlands. The study aim was to analyze human factors as the cause of land fires in knowledge factors, cultural factors, social factors, economic factors, and policy roles. This study is a descriptive analytic study with a qualitative approach. Data was obtained through interviews with key informants who had been sentenced to be fire perpetrators and regular informants from Regional Disaster Management Agency of Regency and Police in Ogan Ilir. The cause of the community burning the land was due to the low level of community understanding regarding the impact of burning the land with the intention of clearing the land and the presence of sonor culture which the community practiced almost every year on the residual harvest. In addition, there are social conflicts between the community and the surrounding land owners, cost savings in land clearing, and the community continues to burn land even though regulations related to land burning already exist. The main factors that cause people to burn are social and economic factors. It is necessary to enforce laws regarding idle land whose ownership is unclear and the local government can provide borrowing heavy equipment at rental prices that are affordable to the community.